PODOBIEŃSTWA TERMINOLOGICZNE W METAJĘZYKU SŁOWIAŃSKIEJ KRYTYKI TERMINOGRAFICZNEJ - Petrova, Tetiana (Przegląd Rusycystyczny, 2020)
The article deals with the issues related to the formation of terminographic criticism as an independent section of terminography. There are no clear boundaries in the metalanguage of terminographic criticism. We conclude that the terminological parallels in the synchronously compared Slavic metalanguages of this direction are formally identical, with absolutely the same semantic structures. It is established that Ukrainian and Belarusian meta-units more often coincide in form than Russian and Polish terms do. In the metalanguage of Slavic criticism, which is under consideration, foreign units prevail. The metalanguage of Ukrainian criticism is rich in synonyms; it is characterized by single intralinguistic homonymy. The identity of the Ukrainian metalanguage, in contrast to the Russian and Belarusian languages, tends to preserve the traditions of national term formation and to adapt borrowed units.